2001
DOI: 10.1039/b108676f
|View full text |Cite
|
Sign up to set email alerts
|

A second distinct structural “state” of high-density amorphous ice at 77 K and 1 bar

Abstract: High-density amorphous ice (HDA), further densi®ed on isobaric heating from 77 K to 165 (177) K at 1.1 (1.9) GPa, relaxes at 77 K and 1 bar to the same structural ``state '' with a density of 1.25 0.01 g cm À3 . Its density is higher by % 9% than that of HDA, and thus it is called very-high-density amorphous ice (VHDA). X-ray diractogram and Raman spectrum of VHDA clearly diers from that of HDA, and the hydrogen-bonded O±O distance increases from 2.82 A Ê in HDA to 2.85 A Ê in VHDA. Implications for the polyam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
368
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 311 publications
(400 citation statements)
references
References 17 publications
(23 reference statements)
28
368
2
2
Order By: Relevance
“…Recently, it has been found that upon annealing or heating isobarically samples of HDA at high-P , the glass becomes denser [49]; the resulting glass is called very-high-density glass (VHDA) or relaxed HDA (RHDA) [26,29,30]. VHDA/RHDA can also be obtained in computer simulations using the SPC/E [30] and the TIP4P models [29].…”
Section: B Annealed Amorphous Icementioning
confidence: 99%
“…Recently, it has been found that upon annealing or heating isobarically samples of HDA at high-P , the glass becomes denser [49]; the resulting glass is called very-high-density glass (VHDA) or relaxed HDA (RHDA) [26,29,30]. VHDA/RHDA can also be obtained in computer simulations using the SPC/E [30] and the TIP4P models [29].…”
Section: B Annealed Amorphous Icementioning
confidence: 99%
“…We note that in Ref. [6] the samples annealed at 11 and 19 kbar reached the same density upon decompression. The clear similarity of the RDF of RP decompressed from 19.5 kbar to that of VHDA recovered at p = 0 in experiment [8] manifested in the distinct peak at r = 3.37Å, very close to the first shell peak, allows us to identify this form as VHDA.…”
mentioning
confidence: 99%
“…The radial distribution function (RDF) of HDA' at p = 0 is shown in Fig.2; it has a broad second peak between 3.3 and 4.6Å, very similar to that of HDA at p = 0 [7]. Inspired by the experiments [6] that led to the discovery of the VHDA we decided to anneal the HDA' phase at each intermediate pressure between 22.5 kbar and zero [20] in order to search for possible new structures. Annealing was performed by heating up to T = 170 K and subsequent cooling down to 80 K; the temperature was always changed in steps of 10 K. The phase obtained in this way will be called relaxed phase (RP).…”
mentioning
confidence: 99%
See 2 more Smart Citations